TESTING VALIDITY OF GROWTH, CONSERVATION, FEEDBACK AND NEUTRALITY HYPOTHESES FOR SELECTED SOUTH ASIAN, EAST AND PACIFIC REGION COUNTRIES - Saira Bibi; Rehmat Ullah Awan; Falak Sher; Jehanzaib Khan (International Journal of Contemporary Issues in Social Sciences, 2024)
Current endeavor attempts to explore the relationship of Gross Domestic Product (GDP), Gross Capital Formation(GCF), labor force(LF)and Energy Consumption(EC)in Selected South Asian; East Asian and Pacific Region for time span 1990 to 2021. Results of Breusch-Pagan LM test confirms cross-sectional dependence for lower middle income countries, upper middle income countries and high income countries. Results of co-integration tests confirms long run relationship between GDP, GCF, Labor Force and EC in selected countries. Results of FMOLS, DOLS and ARDL suggests positive and significant effect of GCF, LF and EC on GDP for Selected countries in long run. Pairwise Dumitrescu Hurlin’s Panel Causality test shows Unidirectional Causality running from EC to GDP, LF to EC, Bidirectional Causality running from GCF to GDP, EC to GCF while remaining variables show neutral causality in LMIC. Pairwise Dumitrescu Hurlin’s Panel causality test shows Unidirectional Causality running from Labor Force to EC while the remaining variables show neutral causality in UMIC. Pairwise Dumitrescu Hurlin’s Panel causality shows Unidirectional Causality running from GDP to EC and LF, GCF to EC while the remaining variables show neutral causality in HIC. Present study suggests that government should take measures to increase labor productivity in energy sector of economy in order to promote economic growth (EG)and to improve human capital in the form of labor participation in energy sector of economy.